Cyclopentenones, scaffolds for organic syntheses produced by the endophytic fungus mitosporic dothideomycete sp. LRUB20 - Porntep Chomcheon (2018)
Two new natural products, 2-hydroxymethyl-3-methylcyclopent-2-enone (1) (synthetically known) and cis-2-hydroxymethyl-3-methylcyclopentanone (2), and a known compound, asterric acid (3), were isolated from the endophytic fungus mitosporic Dothideomycete sp. LRUB20, which was isolated from the stem of the Thai medicinal plant Leea rubra. Compound 2 was separated and identified in the form of its 2,4-dinitrophenylhydrazone derivative (5). Compounds 1, 3, and hydrazone 5 exhibited mild antimycobacterial activity, both with MIC values of 200 μg/mL. Compounds 1, 3, and 4 were inactive (at 50 μg/mL) toward Vero, KB, NCI-H187, and BC cell lines. Hydrazone 5 showed only mild cytotoxicity against the Vero cell line with an IC50 value of 21.7 μg/mL; however, it was inactive toward KB, NCI-H187, and BC cell lines. Endophytic fungi may be a source for the production of building blocks for organic syntheses. © 2006 American Chemical Society and American Society of Pharmacognosy.